2005
DOI: 10.1055/s-2005-870241
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Use of the M2A Patency Capsule System Before a Capsule Endoscopy Procedure, in Patients with Known or Suspected Intestinal Stenosis

Abstract: The current technical development of the patency capsule limits its use in clinical practice, as it did not detect stenoses undiagnosed by CT or SBFT. The start of dissolution at 40 hours after ingestion is too slow to prevent episodes of intestinal occlusion. Patients with Crohn's disease are most likely to be at risk of blockage of progression of the capsule and should benefit from a CT investigation before VCE. However, a careful interview eliciting the patient's medical history and symptoms remains the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 13 publications
2
52
0
5
Order By: Relevance
“…In all of these the video capsule passed through the small-bowel stricture without complication. The rate of patients with the PC excreted intact was similar in the seria of Boivin et al [25] (16/22, 73%), Delvaux et al [26] (16/22, 73%), Signorelli et al [27] (26/32, 81%). In our center, the percentage of cases with PC excreted intact was significant lower (13/29, 45%), probably because of patient selection [28] .…”
Section: Clinical Trials With Patency Capsulementioning
confidence: 60%
See 1 more Smart Citation
“…In all of these the video capsule passed through the small-bowel stricture without complication. The rate of patients with the PC excreted intact was similar in the seria of Boivin et al [25] (16/22, 73%), Delvaux et al [26] (16/22, 73%), Signorelli et al [27] (26/32, 81%). In our center, the percentage of cases with PC excreted intact was significant lower (13/29, 45%), probably because of patient selection [28] .…”
Section: Clinical Trials With Patency Capsulementioning
confidence: 60%
“…A prospective, multi-center trial was designed to assess the clinical usefulness and safety of the PC capsule in patients with intestinal strictures suspected from clinical and/or radiological data. The global data of this trial have not been published, but the results of four of these centers have been reported (Table 1) [24][25][26][27] . In the series reported by Spada et al [24] , 30 out of 34 (88.2%) patients with known or suspected small bowel stricture retrieved the capsule in the stool.…”
Section: Clinical Trials With Patency Capsulementioning
confidence: 99%
“…However, in the study of Bovin et al [14] , in one of the 22 cases with suspected obstructive intestinal disease and/or radiological evidence of smallbowel strictures, impaction of an intact capsule led to ileus and emergency surgery. Similarly, in the study of Delvaux et al [15] , of all 22 patients with known or suspected stenosis, the patency capsule induced a symptomatic intestinal occlusion in three patients, which was resolved spontaneously in one and required emergency surgery in two. It was shown that the start of dissolution at 40 h after ingestion was too late to prevent intestinal occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is not a risk-free procedure, as there have been reported cases of temporary intestinal occlusion and in a study conducted on 22 patients evaluating the usefulness of the patency capsule in patients with suspected small bowel stenosis, 3 patients had intestinal occlusion which required emergency surgery in 2 [21].…”
Section: Discussionmentioning
confidence: 99%